2012
DOI: 10.1155/2012/693631
|View full text |Cite
|
Sign up to set email alerts
|

Urine Telomerase for Diagnosis and Surveillance of Bladder Cancer

Abstract: Bladder cancer has increased incidence during last decades. For those patients with nonmuscle involved tumors, noninvasive diagnosis test and surveillance methods must be designed to avoid current cystoscopies that nowadays are done regularly in a lot of patients. Novel urine biomarkers have been developed during last years. Telomerase is important in cancer biology, improving the division capacity of cancer cells. Even urinary telomerase could be a potentially useful urinary tumor marker; its use for diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
9
0
2
Order By: Relevance
“…Shimada et al (39) reported that surveillance of serum p53 antibodies may be useful in detecting various types of malignant tumors, including bladder cancer. Telomerase is activated in cancer cells, but not in normal somatic cells; therefore, its detection may be used as a diagnostic marker for cancer (40). Patients with urothelial tumors of all grades exhibit telomerase activity in voided urine (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shimada et al (39) reported that surveillance of serum p53 antibodies may be useful in detecting various types of malignant tumors, including bladder cancer. Telomerase is activated in cancer cells, but not in normal somatic cells; therefore, its detection may be used as a diagnostic marker for cancer (40). Patients with urothelial tumors of all grades exhibit telomerase activity in voided urine (41).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study are in agreement with the results of this meta-analysis. It was also stated that, although urinary telomerase could be a potentially useful urinary tumor marker, its use for diagnosis in symptomatic patients or its impact during surveillance is still unknown (40). Furthermore, normalization and standardization of the assays used to evaluate this is required before they may become valuable in clinical practice (40).…”
Section: Discussionmentioning
confidence: 99%
“…Цистоскопия -малоинвазивный метод, который, тем не менее, требует местной анестезии и часто приводит к побочным эффектам. Тем не менее, этот метод является одним из основных при диагностике РМП, так как доступные неинвазивные методы, разработанные за последние 10 лет, не обладают достаточной чувствительностью и специфичностью [1,4,5]. Из-за высокого риска рецидивирования РМП необходима разработка более эффективных неинвазивных методов диагностики РМП, способных заменить инвазивные и малоинвазивные методы, а также Для разработки методики неинвазивной диагностики рака мочевого пузыря был проведён анализ активности теломеразы в образцах ткани опухоли мочевого пузыря и клеточных осадках мочи пациентов неизотопным методом TRAP (telomerase repeat amplification protocol).…”
Section: Introductionunclassified
“…необходимые для прогнозирования течения болезни и последующего врачебного наблюдения за пациентами [5,6]. Временной фактор является важным для диагностики и успешности лечения РМП, поэтому выявление онкомаркёров на ранней стадии заболевания является актуальной задачей современной онкологии [6].…”
Section: Introductionunclassified
“…Bladder cancer is a frequent and very aggressive malignant tumor representing during 2011 the fourth most common malignancy in men and the ninth in women [ 1 ]. More than 90% of bladder malignancies are urothelial bladder carcinomas (UBC) characterized by proliferation of inner superficial layer of urinary bladder (urothelium) that is constantly exposed to metabolites and other chemicals through contact with urine [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%